2023
DOI: 10.3390/ijms24021341
|View full text |Cite
|
Sign up to set email alerts
|

S100A6 Protein—Expression and Function in Norm and Pathology

Abstract: S100A6, also known as calcyclin, is a calcium-binding protein belonging to the S100 protein family. It was first identified and purified more than 30 years ago. Initial structural studies, focused mostly on the mode and affinity of Ca2+ binding and resolution of the resultant conformational changes, were soon complemented by research on its expression, localization and identification of binding partners. With time, the use of biophysical methods helped to resolve the structure and versatility of S100A6 complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 189 publications
1
3
0
Order By: Relevance
“…Here we detected an increase in S100A6 expression in the tears of patients with RA-SS relative to the concentration of this protein in healthy subjects. S100A6 has been demonstrated to fulfill a role in other inflammatory autoimmune diseases such as primary biliary cholangitis and systemic sclerosis of the lung [ 66 ], consistent with our observations. Other than S100A6, S100A8/9/calprotectin has also been studied in inflammatory diseases, especially in RA, confirming the influence of this protein family in the pathology [ 67 , 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…Here we detected an increase in S100A6 expression in the tears of patients with RA-SS relative to the concentration of this protein in healthy subjects. S100A6 has been demonstrated to fulfill a role in other inflammatory autoimmune diseases such as primary biliary cholangitis and systemic sclerosis of the lung [ 66 ], consistent with our observations. Other than S100A6, S100A8/9/calprotectin has also been studied in inflammatory diseases, especially in RA, confirming the influence of this protein family in the pathology [ 67 , 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…To explore this possibility, in this work, we test the affinity of another promiscuous S100 oncoprotein [ 50 , 51 ], S100A6 (also known as calcyclin; it has a pairwise sequence identity to S100P of 35% [ 52 , 53 ]), specific to the six four-helical cytokines shown in Table 1 , to 35 four-helical cytokines from all their structural families ( Table S1 ). Our findings greatly expand the long list of known extracellular target proteins of S100A6, which may be of value for deciphering its role in the progression of many cancers, neurodegenerative disorders, myocardial infarction, acute coronary syndrome, chronic renal disease, primary biliary cholangitis, pulmonary fibrosis, systemic sclerosis of the lung, endometriosis, osteoarthritis, various eye pathologies, and other disorders (reviewed in [ 54 , 55 , 56 ]).…”
Section: Introductionmentioning
confidence: 76%
“…Of the 117 serum differential proteins we identified, many have been corroborated in epilepsy patients and animal models. S100A6 (calcineurin) is an EF-hand calcium-binding protein that is thought to have multiple functions, including calcium homeostasis and neuronal degeneration (22). One study based on an epileptic rat model showed that S100A6 protein levels were significantly elevated in the cortex and hippocampal CA1 region on day 14 after amygdala stimulation (23).…”
Section: Discussionmentioning
confidence: 99%